Addressing the self-directed learning culture gap in Kenya's Junior School Science Curriculum - Cosmas Masega Ongesa; Joseph Mwinzi; Samson Gunga; Atieno Kili K’Odhiambo (European Scientific Journal, ESJ, 2025)
This is a philosophical study and involves conceptual analysis of existing documents on Competency-Based Curriculum (CBC), Kenya’s curriculum reforms and self-directed learning culture (SDLC). The study mainly focuses on how the curriculum reforms and curriculum for Kenyan CBC junior schools integrate science, and the current theoretical instructional model has promoted the development of SDLC. The data collected and analyzed is theoretical. This conceptual analysis applies the Kantian critical judgment theory model to analyses the data collected and assess findings using the reflective self-directed instructional model (RSIM). RSIM has standard sub-themes and learning strategies used in assessing SDLC. Key sub-themes and learning strategies used as standard are self-motivation, self-reflection, self-regulation, active learning, metacognition, and collaborative community of inquiry. Key theoretical premises and claims, co-premises, propositions, and supporting evidence are developed using the categories scrutinized and analyzed. According to the analysis, the study reveals a significant gap in the integration of SDLC within the CBC reforms and curriculum design. The study, therefore, proposes a novel instructional model to address this shortfall.